2004
DOI: 10.1097/01.coc.0000055059.97106.15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Factors in Patients With Malignant Glioma Treated With Combined Modality Approach

Abstract: The impact of various clinical pretreatment prognostic factors in patients with malignant glioma treated with a combined modality approach was investigated in 229 patients treated on four consecutive prospective phase II studies. The median survival time for all 229 patients is 14 months, and 2- and 5-year survival rates are 34%, and 9%, respectively. The median time to tumor progression is 14 months, and 2- and 5-year progression-free survival rates are 32%, and 9%, respectively. Females did better than males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 76 publications
3
38
0
1
Order By: Relevance
“…Barker et al 1 mention age as an independent variable to obtain good results in radiotherapy. Some studies 6 inform that age influences the tumor removal extension, which may partly explain more survivals in younger patients in our series. There was no difference in the tumor removal extension related to age ( Table 2).…”
Section: Discussionmentioning
confidence: 77%
See 4 more Smart Citations
“…Barker et al 1 mention age as an independent variable to obtain good results in radiotherapy. Some studies 6 inform that age influences the tumor removal extension, which may partly explain more survivals in younger patients in our series. There was no difference in the tumor removal extension related to age ( Table 2).…”
Section: Discussionmentioning
confidence: 77%
“…Several authors declare that patients with higher KPS showed longer survival rather those with lower KPS. 2,6,8,10,14 According to Kreth et al 9 the youngest individuals tend to show higher KPS, which may be considered a confusing variable in the multivariate statistical analysis models. In Lacroix et al series 10 75% of patients showed KPS higher than 80.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations